STUDY OF THE SYNTHESIS OF BIS-CARBAMATE OF THE MEE SERIES AND STUDY OF BRUTTO INHIBITORY ACTIVITY (Journal of Science-Innovative Research in Uzbekistan, 2024)
This research work is devoted to the synthesis of a new bis-carbamate  N,N'-hexamethylene bis-[(ortho-cresol)-carbamate] i.e. MEE-1 based on  diisocyanates and cresols. A possible mechanism of inhibited oxidation for polymers  in two stages has been proposed. And also, the brutto (gross) inhibitory activity in  model reactions of thermal autoxidation of low-density polyethylene was studied.  As a result, it turned out that MEE-1 bis-carbamate increases the thermal-oxidative  stability of low-density polyethylene by 2.5-43.2 times compared to other industrial  antioxidants and arouses practical interest for further study.